Expression of Metallothionein MTT1 and MTT2 from Tetrahymena thermophila Exposed to SO2, NaCl and Tris-HCl - Wang, Qinglu; Xu, Jing; Chai, Baofeng; Liang, Aihua; Wang, Wei (Asian Journal of Chemistry, 2011)
The mRNA levels of two components of Tetrahymena thermophila metallothionein (MT) gene families, MTT1 and MTT2, were evaluated using real-time quantitative-PCR when cells were exposed to SO2 derivatives, high-salt and Tris-HCl. The MTT1 expression level was higher by SO2 derivatives and Tris-HCl stress than MTT2. The influence of high-salt for MTT1 and MTT2 mRNA levels were weak. The results provided evidence that MTT1 protein act as an important role against the damage of SO2 derivatives and beginning of starvation and MTT1 and MTT2 protein act a small role in anti-high-salt.